Housing microfinance and the empowerment of low-income households in Kenya - ODONGO, Nicholas Ouma (KDI School, 2018)
It has been reported that only 10.2% of all Kenyan urban households can afford the cheapest newly built house constructed by formal developers. Majority of Kenyans have limited access to adequate housing and cannot afford an average loan to finance a decent house; this has pushed many low-income households into the slums. The country is left to grapple with an annual deficit of an approximate 200,000 housing units for its urban areas. With the affordability issue rife, credit reform has become a critical discussion point in Kenya and most other developing countries. In light of this, housing microfinance has emerged as an effective and sustainable solution responsive to the needs of the poor. Many sub-Saharan African countries including South Africa, Uganda, Angola, and Ghana have made significant policy efforts to exploit the HMF market. The purpose of this paper is to investigate the impact of HMF among low-income households (LIHs) in Kenya. And the aim is to draw attention to the effectiveness of HMF in addressing housing needs for the poor, thereby calling for government intervention in the housing microfinance sub-sector. To gather information about borrowers, microfinance institutions, and HMF portfolios, this study conducted a literature review of current research, surveys and databases. Data gathered was described and explored qualitatively to establish the socio-economic impact of housing microfinance on the borrowers. The results show that housing microfinance contributes to affordable housing through relatively cheaper credit; empowers home owners with dweller-control of the construction process; and improves the quality of homes of low income households. The study also finds that HMF enhances household empowerment measured in terms of financial inclusion (more opportunities to access savings and credit services), social inclusion and economic security. Finally, the paper advocates for a government-led integrated support structure for the HMF subsector as a means to address challenges faced by the poor in financing development. This support takes two forms; a housing microfinance loan guarantee system and institutional capacity building for HMF institutions. The housing microfinance loan guarantee scheme seeks to provide lenders with guarantees of loan repayment to assist in financing housing construction/ rehabilitation for the more risky and less profitable lower income households. HMF institutional capacity building seeks to assist HMF institutions in the areas of risk management and underwriting to minimize non-performing loans and remain profitable while providing a social good – housing.
Thesis(Master) --KDI School:Master of Public Policy,2018